Smartphone as a tool for evaluating oblique muscle dysfunction - Rautha,Yessa Vervloet Bertollo Lamego (2022)
ABSTRACT Purpose: The aim of this study was to describe a simple, accessible, and reliable method using a smartphone for evaluating oblique muscle dysfunctions. Methods: The photograph rotation tool in the iPhone PHOTO app was used by 75 examiners to evaluate 22 photographs from only 9 patients, captured in infra- and supra-dextroversion, and infra- and supra-levoversion, as not all the patients were photographed in the 4 positions mentioned. Each patient received a score for the superior and inferior oblique muscle functions, ranging from -4 (hypofunction) to 4 (hyperfunction) or 0 (normal function), using preediting and postediting photographs. These values were compared with the scores previously given by trained personnel in strabismus screening. The difference in score between the two groups was expressed in natural (whole and non-negative) numbers. The mean and pattern deviation were then calculated. Results: The scores of most of the edited photos showed a lower mean than those of the unedited ones, except for a patient with left superior oblique hyperfunction. The patients with no oblique dysfunction and those with right superior oblique hyperfunction demonstrated (after editing the photograph) scores with greater similarity with their initial scores (p<0.05 and p<0.01, respectively). Similar results were found in the patients with oblique hypofunctions and right inferior oblique hyperfunction (p<0.01). Conclusion: The proposed method for assessing muscular function in vertical strabismus is reproducible, accessible, simple, and reliable, and provides better consistency to the admeasurement.